GROWTH AND PRODUCTION OF LESSER DUCKWEED (Lemna minor) IN DIFFERENT MANURE SOLUTIONS AND CONCENTRATIONS - Gena, Freddy; Karno, Karno; Sumarsono, Sumarsono (Animal Agriculture Journal, 2013)
ABSTRACTThis study was done at the glass house of University of Diponegoro, Semarang. The research was about investigating the performance of Lemna minor from Lemna spp. of Lemnaceae family when grown for 14 days under 3 different manure types and concentration levels. The beef cattle manure, chicken manure and dairy cattle manure were mixed with 30 liters tap water in a triplicate media concentration of 0g/l, 5g/l and 10 g/l. In addition to the manures 1 kg top soil was added in all experimental units and 20 g of Lemna minor was planted as the initial plant weight. The manure type and manure concentration level were arranged in a 3x3 factorial completely randomized design arrangement and mean comparisons was done with Duncan Multiple Range Test. The results in ANOVA showed that there was significant interaction (F=6.31, p=.0023) as well as significant main effects (F=21.51, p=.0001; F=52.78, p=.001) for FY. For the GR the manure type x concentration level interaction was significant (F=6.30, p=.0024) and type of manure and level of concentration main effects were also significant (F=21.45, p=.0001; F=52.63, p=.0001). Significant interaction was also noticed for CPC (F=28, p=.0001) and significant main effects of manure and concentration (F=72.64, p=.0001; F=29.12, p=.0001). The average pH of the manure solutions before planting and after harvesting was 6.07 and 6.48 respectively. Prior to preparing the mediums duplicate samples of various manure as well as top soil were tested for Kjeldahl Nitrogen on dry matter basis.Key words: Lemnaceae, Lemna minor, Lemna spp., manure